A simple, rapid and low-cost qPCR assay for evaluating the severity of exosomal PD-L1-mediated T cell exhaustion in blood samples. Issue 6 (21st December 2021) - Zhan, Renhui; Wang, Shanshan; Guo, Wenfei; Gao, Xiaonan; Liu, Xiaojun; Xu, Kehua; Tang, Bo
Abstract : A novel qPCR assay was developed for the quantitative analysis of exosomal PD-L1 on T cell-exosome complexes in blood samples. Abstract : A novel dual-aptamer activated proximity-induced qPCR assay was developed for the quantitative analysis of exosomal PD-L1 on T cell-exosome complexes in blood samples.